2017
DOI: 10.24925/turjaf.v5i2.164-169.989
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Improved Rice Variety on Productivity Among Smallholder Farmers in Ghana

Abstract: Advancement in agricultural technologies is seen to result in the shift in production functions. The study was conducted to establish the impact of the improved rice variety on productivity in the Ejura-Sekyedumase and Atebubu-Amantin Municipalities of Ghana. The study was based on the survey of 208 rice farmers using a three-stage stratified sampling method. The study used a structured questionnaire to collect input-output data from the rice farmers. Data were analysed using the Cobb-Douglas production functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Some studies indicated that higher usage of these inputs increased fertilizer and pesticide costs [39,40].High cost of inputs(fertilizer, pesticides) is the second financial constraints facing rice farmers,the findings are similar to [41,42]. Rice farmers use of improved varieties leads to increasing productivity [43] and farm output [44]. The high cost of improved varieties ranked three among financial constrains facing rice farmers, [5] pointed to the same constraint.…”
Section: Discussionmentioning
confidence: 74%
“…Some studies indicated that higher usage of these inputs increased fertilizer and pesticide costs [39,40].High cost of inputs(fertilizer, pesticides) is the second financial constraints facing rice farmers,the findings are similar to [41,42]. Rice farmers use of improved varieties leads to increasing productivity [43] and farm output [44]. The high cost of improved varieties ranked three among financial constrains facing rice farmers, [5] pointed to the same constraint.…”
Section: Discussionmentioning
confidence: 74%